STRUKTUR BIBIR Osteochilus partilineatus KOTTELAT DAN PERBANDINGANNYA DENGAN 7 JENIS Osteochilus LAINNYA - Renny Kurnia Hadiaty (Research Center for Biology-Indonesian Institute of Sciences, 2003)
Osteochilus is a genus of fish with large lips,everted, sucker-like, covered with more or less folds of plicae bearing numberous unicellulair keratinous projections or uncuil. The structure of thr lips Osteochilus is divided into three from i.e. ectomorph, mesomorph and endomorph, based on the length and shape of plicae on the lateral portion of the upper lip, the distribution of uncuil and taste buds on the plicae , also from the size and shape of uncuil. Osteochilus partlilineatus is a small fish which has a nice colour patteern, so it is potential as an ornamental fish. it has an ectomorph lips, which the structure of plicae,uncuil and taste buds. The from of the taste buds redemble the rose flower which are very different with the structures of that 7 other Osteochilus that were examined by Roberts using scaning Electro Microscope (SEM).